Ethno Plunderphonics: On Some Mockingbird Transcriptions. - Skinner, Jonathan (Interval(le)s, 2008)
The article presents information on mockingbird speech. According to the author, the speech of a mockingbird woke him up in the morning five years ago when he was at the Organ Pipe Cactus National Monument in Southern Arizona. The author says that he made efforts to understand the bird song from different angles. It is stated that poet Bronislaw Malinowski thought a lot about the meaning of the words without meaning in the context of his study of Trobriand gardening, and decided that such words had considerable weirdness, strangeness, and unusualness. Emotions were also present in the rhythmic setting of the words. The article also presents several poems related to bird songs.